Bhinneka Tunggal Ika: Keanekaragaman Sukubangsa atau Kebudayaan? - Parsudi Suparlan (Antropologi Indonesia, 2003)
In this article, the author presents his thoughts on cultural diversity as the motto of Indonesia nation, on the basis of the ideology of 'Unity in Diversity' (Bhinneka Tunggal Ika). The author has a notion that the meaning of bhinneka tunggal ika was emphasized as ethnics' diversity during New Order (Orde Baru) and Habibies rezim era. It represents the consequence of ethnical politics with plural society model used by the regimes. The fall down of the New Order regime, caused any social conflicts and national disintegration especially in a period of Habibie governance. To rebuild social solidarities and the Indonesian national integration, the author offers model of multiculturalism in comprehending bhinneka tunggal ika which emphasizing equal cultural diversity. The author stresses that the model of multiculturalism only possible exist and expand in societies which uphold principles of democracy, justice supremation of law, and also eradication of corruption and collusion.